Manajemen Sekolah Unggulan: Strategi Pengembangan Kapasitas Sekolah Menuju Pendidikan Bermutu - Zahroh, Aminatul (Taallum: Jurnal Pendidikan Islam, 2014)
Excellent school is the one which has some excellences in term of facilities, infrastructure, and management. Good management plays important role in especially in deciding the program for developing the school. To boost the development of the school, good cooperation from all parties in the school is highly needed. Through good management, there will be revolutionary movement in education so that education in Indonesia will yield high quality.